KEKUATAN PEMBUKTIAN PEMERIKSAAN SETEMPAT (GERECHTELIJKE PLAATSOPNEMING) DALAM PEMERIKSAAN SENGKETA PERDATA - Ambarita, Marselinus (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
The local examination (gerechtelijke plaatsopneming) is a medium which is provided by the laws and regulations for the judge or the judge panel to clarity a fact or object that is being disputed, in which the local examination or the trial which is conducted by the judge or the judge panel at the object’s spot where is being disputed. The local examination it self is regulated in the Article 153 HIR/Article 180 RBg and also in the circular letter of Indonesia Supreme Court (Surat Edaran Mahkamah Agung/SEMA RI) Number 7 of 2001 on The Local Examination. The local examination has a function to match the plaintiff’s postulates of private lawsuit about the dispute’s object of the private lawsuit which is area just for the land dispute, such as the surface measure, position by mentioning its details as roads, village, sub districts, and then it borders with whose properties. The matters are pointed to ease the judge or the judge panel in deciding the judge decision whether the private lawsuit could be granted or rejected, or whether the private lawsuit itself is obscuur lebel (unclear) so that it is unacceptable.